The Model of Upstream Investment Portfolio in the Mature Regions - Artemkina, Liya R.; Sopilko, Natalya Y.; Myasnikova, Olga Y.; Eremina, Irina U.; Bondarchuk, Nataliya V.; Shamsheev, Sergey V. (International Journal of Energy Economics and Policy, 2019)
Portfolio models can serve as an assessment tool for the optimal assignment of capital between the potential investment projects in the various conditions for upstream companies. This process is crucial for any company if it wants to balance the short-term goals and seeks to maximize long-term value of the company. The paper aims to present a practical model of forming oil upstream company's portfolio. The unique feature of this model is an individual approach to investment plan forming in a context of three types of projects: exploration, oil production and infrastructure projects. This is due to the individual approach which is used for comparison of all projects by using of universal set of indicators. Suggested model uses the multi-criteria selection mechanism by means of aggregating the key estimating indicators into the final project rank score. In that way the task of forming investment project's portfolio of upstream company is a linear programming problem that is solved by simplex method. In the paper the model forms consolidated investment portfolio that takes into account decision makers' preferences in setting of limits for resources. Keywords: Simplex method, optimizing the investment, project's ranking indicator, decision-making mechanism, optimization model, investment portfolio, upstream company JEL Classifications: O13, L22 DOI: https://doi.org/10.32479/ijeep.7965